Fostering positive CEO‐board relationships: Board synchronization skill and relationship cycles in new ventures - Garg, Sam; Bingham, Christopher B. (Strategic Management Journal, 2025)
Research Summary This article explores how new venture leaders foster positive CEO–board relationships, a critical yet underdeveloped topic in governance research. We examine the ongoing interactions between first‐time CEOs and their boards, focusing on the tension between boards' need for influence and transparency and CEOs' desire for autonomy and control. Introducing the concept of “relationship cycles,” we demonstrate how early interactions create virtuous or vicious feedback loops that shape long‐term governance outcomes. We also propose “board synchronization skill” as a key construct, highlighting how CEOs successfully manage communication to align competing goals. Finally, we set forth a temporal contingency view of live communication that reveals how interaction effectiveness varies by stage, thereby impacting CEO–board dynamics. More broadly, this study offers a process‐oriented view of governance, expanding our understanding of CEO–board relationships in ventures. Managerial Summary This article examines how leaders of new ventures can build and sustain effective CEO‐board relationships—an essential yet often overlooked aspect of corporate governance. Drawing on the experiences of first‐time CEOs, we explore the dynamic tension between a board's need for influence and transparency and a CEO's desire for autonomy and control. We introduce the concept of "relationship cycles" to explain how initial interactions can establish positive or negative feedback loops that influence long‐term governance outcomes. We also identify "board synchronization skill" as a critical capability for CEOs, emphasizing the importance of managing communication to balance competing priorities. Additionally, a stage‐specific approach to live communication is proposed, illustrating how the effectiveness of interactions evolves over time and shapes CEO‐board dynamics. Overall, the study takes a process‐oriented perspective, offering new insights into how governance practices can drive better alignment and performance in entrepreneurial ventures.